1981
DOI: 10.3758/bf03333698
|View full text |Cite
|
Sign up to set email alerts
|

Contingency in fear conditioning: A reexamination

Abstract: The effects on classical fear conditioning of the rate of presentation of the unconditioned stimulus (US) and the contingency between the conditioned stimulus (CS) and the US were examined using the conditioned emotional response procedure with rats. Increases in US rate reduced suppression by the same amount whether the added USs were signaled by CS, thereby maintaining the CS-US contingency, or unsignaled, thereby weakening the CS-US contingency. Failure to control for the rate of US presentation in previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

1981
1981
2003
2003

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 110 publications
(19 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…This view, termed the relative waiting time (RWT) hypothesis by Jenkins, has recently been applied to the conditioned suppression procedure. In this study, Jenkins and Shattuck (1981) concluded that better conditioned suppression occurs with lower RWT ratios, independently of CS-US contingency.…”
Section: Methodsmentioning
confidence: 90%
“…This view, termed the relative waiting time (RWT) hypothesis by Jenkins, has recently been applied to the conditioned suppression procedure. In this study, Jenkins and Shattuck (1981) concluded that better conditioned suppression occurs with lower RWT ratios, independently of CS-US contingency.…”
Section: Methodsmentioning
confidence: 90%
“…Because the average waiting time in the context and that in the target CS are not altered by the signaling of the extra USs, SET predicts that the effect of extra USs is no different whether signaled or unsignaled by a second CS. Several experiments have produced results supporting this conception (Balsam, 1982;Jenkins, 1984;Jenkins et al, 1981;Jenkins & Lambos, 1983;Jenkins & Shattuck, 1981;LoLordo & Randich, 1981). Jenkins et al (1981, Experiment 13) did not obtain significantly less acquisition to a target CS when extra USs were signaled as compared to when they were unsignaled, but such an effect was obtained by Durlach (1983), who used more prolonged target CS conditioning.…”
mentioning
confidence: 84%
“…In Pavlovian conditioning, to be sure, it is well known that the effectiveness of the conditional stimulus (CS) is a function of the length of time by which it has characteristically preceded the unconditional stimulus (US), but Balsam, 1984;Brown, Hemmes, Coleman, Hassin, & Goldhammer, 1982;Gibbon & Balsam, 1981;Jenkins, 1984;Jenkins, Barnes, & Barrera, 1981;Jenkins & Shattuck, 1981. ) As mentioned earlier, under standard Pavlovian procedures stimuli that are negatively correlated or that precede the US by longer than average times are found to be inhibitory (LoLordo & Fairless, 1985;Rescorla, 1969b).…”
mentioning
confidence: 99%